2021
DOI: 10.21203/rs.3.rs-1021148/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Influencing Factors of Wheezing and Asthma Among Preschool Children in Urumqi City: A Cross-sectional Survey

Abstract: Background: To investigate the prevalence and indoor environmental influencing factors of wheezing and asthma among preschool children in Urumqi, Xinjiang, China to provide a strong basis for prevention and control. Methods: In August 2019, a cross-sectional epidemiological study involving 8153 preschool children was conducted in 60 kindergartens in Urumqi. The mean age of the children who participated in the survey was 5.27 ± 1.10 years. Additionally, 51.9% were boys, 86.9% were Han Chinese, and an 81.53% sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Kim et al 13 found a higher prevalence of asthma in boys than in girls, and children with a family history of asthma had a higher risk of developing asthma. Quite a few studies have found that the risk of asthma in minorities is greater than that in the Han population 7 , 14 . This is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 13 found a higher prevalence of asthma in boys than in girls, and children with a family history of asthma had a higher risk of developing asthma. Quite a few studies have found that the risk of asthma in minorities is greater than that in the Han population 7 , 14 . This is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%